Property Rights Arrangement in Emerging Natural Resources: A Case Study of China’s Nationalization of Wind and Sunlight - Chen, Jianlin; Cui, Jiongzhe (Columbia Journal of Asian Law, 2013)
The passage of the Heilongjiang Province Regulation on Climate Resources Survey and Protection (the “Regulation”) that regulates wind and solar energy generation sparked a public furor because it contains a provision that stipulates, “climate resources are owned by the state.” As a case study of this regulatory attempt to manage emerging natural resources, this Article makes the following three arguments. First, the “nationalization” provision in the Regulation is legally compatible with Chinese law that conceives of public property as state-owned property and not as property that requires public access. Second, a clear designation of the state as the manager of resources on behalf of the otherwise amorphous notion of the public is preferable to the “tragedy of the commons” that might arise from the free public access to such natural resources that is advocated by certain Chinese scholars. Third, this controversy is largely irrelevant because the state is always able to address redistribution and externality concerns related to resource use through taxation and various regulatory powers, regardless of whether natural resources are publicly or privately owned. On a broader note, this Article cautions against the pitfall of instinctively rejecting all state intervention – even when there is legitimate distrust regarding state governance – and highlights how the issue of governance remains central regardless of the property rights arrangement for emerging natural resources.